Dimethyl sulfoxide pivaloyl chloride: a new reagent for oxidation of alcohols to carbonyls - Dubey, Abhishek; Kandula, Subba Rao V.; Kumar, Pradeep (Synthetic Communications, 2008)
An efficient procedure for conversion of alcohols to the corresponding carbonyl compounds, an alternative to the classical Swern oxidation, is described. Pivaloyl chloride is employed as a mild and inexpensive electrophile. A possible reaction mechanism is proposed.
Keywords: Alcohols; carbonyls; DMSO; pivaloyl chloride; Swern oxidation

Cobalt(II) chloride hexahydrate-diisopropylamine catalyzed mild and chemoselective reduction of carboxylic esters with sodium borohydride - Jagdale, Arun R.; Paraskar, Abhimanyu S.; Sudalai, Arumugam (Synthesis-Stuttgart, 2009)
The cobalt-catalyzed reduction of unsaturated alpha-cyano carboxylic esters using sodium borohydride (NaBH(4)) leads to the corresponding saturated cyano alcohols in high yields. In particular, the new catalytic system cobalt(II) chloride-diisopropylamine in combination with NaBH(4) showed excellent activity in the chemoselective reduction of a variety of carboxylic esters to their corresponding alcohols in good to excellent yields under mild conditions.
Keywords: Alcohols; amines; catalysis; Esters; reductions

Solvent-free selective oxidation of primary alcohols-to-aldehydes and aldehydes-to-carboxylic acids by molecular oxygen over MgO-supported nano-gold catalyst - Choudhary, Vasant R.; Dumbre, Deepa K. (Catalysis Communications, 2011)
Magnesium oxide supported nano-gold catalyst (prepared by the homogeneous deposition precipitation technique) showed high activity/selectivity and excellent reusability in the oxidation of different primary alcohols and aldehydes to corresponding aldehydes and carboxylic acids, respectively, by molecular oxygen (under atmospheric pressure) in the absence of any solvent. Influence of the catalyst calcination temperature (400-900 degrees C), reaction temperature (50-120 degrees C) and use of different solvents (viz. toluene. p-xylene, DMF or DMSO) on the oxidation reaction has also been studied. (C) 2011 Published by Elsevier B.V.
Keywords: Alcohols; aldehydes; Au/MgO; Molecular oxygen; Solvent-free oxidation

Highly efficient catalyst derived from Ni-Fe-hydrotalcite for solvent-free O- or S-acetylation of alcohols, phenols and thiols at room temperature - Choudhary, Vasant R. (Proceedings of the National Academy of Sciences India Section A-Physical Sciences, 2013)
Solvent-free O-acetylation of alcohols (including secondary and tertiary alcohols) and phenols and S- acetylation of thiols by acetyl chloride with high product yields at room temperature in a very short reaction period can be easily accomplished using a small amount of solid catalyst obtained from the decomposition (at 600 A degrees C) of Ni-Fe-hydrotalcite. Both the reactions are carried out at room temperature under solvent-free conditions. The catalyst can be easily separated from the reaction mixture, simply by filtration and reused several times without a significant loss of its activity.
Keywords: Acetyl chloride; Alcohols; Ni-Fe- ht derived catalyst; O- and S-acetylation; Phenols; Solvent-free

Simple cobalt(II) chloride catalyzed N-alkylation of amines with alcohols - Midya, Siba P.; Mondal, Akash; Begum, Ayesha; Balaraman, Ekambaram (Synthesis-Stuttgart, 2017)
A facile cobalt-catalyzed N-alkylation of amines with alcohols using inexpensive, commercially available CoCl2 center dot 6H(2)O is reported. Employing this readily available cobalt catalyst, a variety of amines with wide functional group tolerance were selectively alkylated under benign conditions.
Keywords: (Hetero)Aromatic Amines; Alcohols; Amination; amines; Anilines; Aromatic-amines; Cobalt Catalysis; Dehydrogenation Borrowing Hydrogen; Efficient Catalysts; Hydrogen Autotransfer; Iridium; N-alkylation; Pincer-complex; Secondary Alcohols; Selective Alkylation

Altering the O/C ratio of lignin derived monomers without sacrificing atom efficiency - Singh, Dheerendra; Dhepe, Paresh L. (ChemistrySelect, 2019)
Synthesis of platform and fuel grade chemicals from lignin without losing atom efficiency and lowering O/C ratio is a challenge in a bio-refinery concept. In this work, we report solid acid catalysed alkylation of lignin derived variety of monomers such as guaiacol, veretrole, phenol, anisole, and catechol using numerous alcohols as alkylating agents. Results elaborate that the type of acidity and structure of catalyst play important role in achieving higher dialkylated products (DAP). With 85% conversion of guaiacol, 30.9% DAP formation was achieved at 250 degrees C within 2 h. A unique substrate adsorption study on the catalyst surface and effect of solubility of substrates on the activity of catalyst is evaluated. Catalyst was observed to be recyclable with marginal loss in the activity due to handling error.
Keywords: Alcohols; Alkylation; lignin; Monomers; solid acid catalyst; Up-gradation

Chemodivergent dehydrogenative coupling of alcohols by 3d metal catalysts - Bansal, Sadhna; Punji, Benudhar (ChemCatChem, 2024)
Chemodivergent synthesis by transition metal catalysts is a straightforward and sustainable approach to achieving valuable organic compounds. Especially, the chemodivergent dehydrogenative couplings of alcohols with organic motifs to develop various saturated and unsaturated compounds are highly environmentally benign due to the reduced waste generation. In this concept review, we presented the 3d transition metal (Mn, Fe, Co, and Ni)-catalyzed chemodivergent synthesis of imines and amines, saturated and unsaturated carbonyl/alcohol compounds, saturated and unsaturated nitriles, N-heterocycles, and N-/C-alkylated indoles. The discussed reaction commanded two or three different products with high chemoselectivity by changing specific reaction parameters, but keeping the catalyst unchanged. Generally, the acceptorless dehydrogenative coupling (ADC) provides unsaturated moieties, whereas the borrowing-hydrogen (BH) process results in saturated compounds. Text for Table of Contents: An overview of the chemodivergent dehydrogenative coupling of alcohols by the Earth-abundant transition metal catalysts is discussed. image
Keywords: 3d metals; Alcohols; chemodivergent; dehydrogenative coupling; heterocycles

Dehydrogenative coupling of alcohols with internal alkynes under nickel catalysis: an access to β-deuterated branched ketones - Subaramanian, Murugan; Gouda, Chandrakant; Roy, Triptesh Kumar; Ganesan, Sivakumar; Banerjee, Subhrashis; Vanka, Kumar; Balaraman, Ekambaram (ACS Catalysis, 2024)
In synthetic organic chemistry, unconventional strategies for advanced chemical synthesis pose interesting and challenging problems. Alcohols act as alkylating agents in the C-C and C-N bond-forming reactions via the dehydrogenative borrowing hydrogen strategy in traditional transition metal catalysis; however, as an acylating agent in the C-C bond-forming reactions is challenging and rarely reported. Here, we report the dehydrogenative coupling of benzylic alcohols with internal alkynes under nickel(II) catalysis, wherein alcohol is used as an acylating agent. This reaction system affords a wide range of alpha-branched aryl ketone derivatives with zero waste generation through the umpolung borrowing hydrogen strategy. Moreover, we have demonstrated the chemodivergent applications of the alpha-disubstituted ketones to other valuable building blocks, including large-scale synthesis of beta-deuterated branched ketones. Several spectroscopic studies, intermediate identification, and density functional theory calculations were performed to elucidate the reaction mechanism.
Keywords: Alcohols; alpha-branched aryl ketones; dehydrogenative coupling; internal alkynes; nickel catalysis; pseudoumpolung

Nickel-catalyzed chemodivergent coupling of alcohols: efficient routes to access α,α-disubstituted ketones and α-substituted chalcones - Bansal, Sadhna; Punji, Benudhar (Chemistry- a european journal, 2024)
Chemodivergent (de)hydrogenative coupling of primary and secondary alcohols is achieved utilizing an inexpensive nickel catalyst, (6-OH-bpy)NiCl2. This protocol demonstrates the synthesis of branched carbonyl compounds, alpha,alpha-disubstituted ketones, and alpha-substituted chalcones via borrowing hydrogen strategy and acceptorless dehydrogenative coupling, respectively. A wide range of aryl-based secondary alcohols are coupled with various primary alcohols in this tandem dehydrogenation/hydrogenation reaction. The nickel catalyst, along with KOtBu or K2CO3, governed the selectivity for the formation of branched saturated ketones or chalcones. A preliminary mechanistic investigation confirms the reversible dehydrogenation of alcohols to carbonyls via metal-ligand cooperation (MLC) and the involvement of radical intermediates during the reaction. The chemodivergent nickel-catalyzed approach provides alpha,alpha-disubstituted ketones from aryl-substituted secondary alcohols and benzyl alcohols via the borrowing hydrogen (BH) strategy in the presence of KOtBu, whereas exclusively alpha-substituted chalcones were accomplished in the presence of mild base K2CO3 through an acceptorless dehydrogenative coupling (ADC) strategy. image
Keywords: Alcohols; dehydrogenative coupling; Metal-ligand cooperation; Nickel; substituted carbonyl compounds